2015
DOI: 10.1063/1.4935498
|View full text |Cite
|
Sign up to set email alerts
|

On jet impingement and thin film breakup on a horizontal superhydrophobic surface

Abstract: When a vertical laminar jet impinges on a horizontal surface, it will spread out in a thin film. If the surface is hydrophobic and a downstream depth is not maintained, the film will radially expand until it breaks up into filaments or droplets. We present the first analysis and model that describes the location of this transition for both isotropic and anisotropic structured superhydrophobic (SH) surfaces. All surfaces explored are hydrophobic or SH, where the SH surfaces exhibit an apparent slip at the plane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
(78 reference statements)
1
10
0
1
Order By: Relevance
“…Unlike a circular hydraulic jump, the liquid thin film breaks up into droplets that are ejected randomly from the rim due to their high momentum. This phenomenon has also been observed by other researchers [17,40] while studying jet impingement on superhydrophobic surfaces.…”
Section: Resultssupporting
confidence: 80%
See 4 more Smart Citations
“…Unlike a circular hydraulic jump, the liquid thin film breaks up into droplets that are ejected randomly from the rim due to their high momentum. This phenomenon has also been observed by other researchers [17,40] while studying jet impingement on superhydrophobic surfaces.…”
Section: Resultssupporting
confidence: 80%
“…Predicting the slip velocity requires estimation of the slip length at the surface, as discussed in Refs. [40,46]. A previous study by Joseph et al [68] suggested that the effective slip length [44], b ef f , is related to the lateral length scale between the surface structures, L, through b ef f = αL, where α 0.28 leads to the best fitting of the experimental results.…”
Section: Theoretical Formulationmentioning
confidence: 96%
See 3 more Smart Citations